Associations between mstn/haeiii polymorphism and reproductive and growth characteristics in morkaraman sheep - Esra SAYGILI; Dogan TURKYILMAZ; Kubra EKINCI; Ulku DAGDELEN TURKYILMAZ; Memiş OZDEMIR; Nurinisa ESENBUGA; Sinan KOPUZLU (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2022)
The myostatin gene inhibits skeletal muscle growth in advanced animals, and a mutation in the gene coding region increases muscle formation. Hence, it is accepted to be a candidate gene for the selection of some production traits. The objective of the current research was to examine the genotypes of the myostatin gene and reveal the associations between the genotypes and a number of traits, including birth weight, weaning weight, weaning age, average daily weight gain, and productivity, in 110 Morkaraman sheep. Genotypes were determined by the PCR-RFLP method using the HaeIII restriction enzyme, and the genotype frequencies were found to be 9%, 69%, and 22% for MM, Mm, and mm in the myostatin locus, respectively. The M allele frequency was 44%, whereas the m allele frequency was 56%. In the studied population, the myostatin locus was not in Hardy-Weinberg equilibrium. The association analysis revealed no statistically significant impact of the MSTN gene polymorphism in exon 3 on birth weight, weaning weight, and productivity (P>0.05) but found a significant effect on weaning age and average daily weight gain (P<0.05). As a result, the MSTN gene showed polymorphisms in Morkaraman sheep and can be regarded as a genetic marker for sheep selection according to the association analysis results.